Comparative analysis of public administration tools in special economic zones of China and Kazakhstan - Aman Konysbek; Bauyrzhan Urazymbetov; Aigul Yessentemirova; Yelena Nechayeva; Svetlana Kozhirova; Zhanna Shaimerdenova (Problems and Perspectives in Management, 2025)
This study examines the role of public administration tools in special economic zones (SEZs) in China and Kazakhstan. The aim of this study is to conduct a comparative analysis of public administration tools in SEZs of both countries, focusing on governance models, regulatory frameworks, investment incentives, and their impact on economic performance. The methodology includes a review of the historical development and current practices of SEZs in both nations, especially comparing the special economic zones of Shenzhen and Astana. This involves analyzing governance structures, tax incentives, and policies impacting FDI and technology transfer using both qualitative and quantitative data. The study concludes that the effectiveness of public administration tools in SEZs depends on governance structures and alignment with national economic goals, highlighting the need for flexible governance models to maximize the economic benefits of SEZs. Findings indicate that China’s decentralized governance was a key factor in its significant and rapid economic growth, providing an example for Kazakhstan to study further and potentially implement, as it grants more decision-making autonomy to local SEZ authorities. The key recommendations are that the adaptivity of public administration strategies plays a vital role in fostering the efficiency of SEZs and attracting high technological industries for Kazakhstan. AcknowledgmentThis research is funded by the Committee of Science of the Ministry of Science and Higher Education of the Republic of Kazakhstan (Project No. BR24993082).